Polybrominated diphenyl ether (PBDE) flame retardants:environmental contamination, human body burden and potentialadverse health effects - Costa, L. G.; Giordano, G.; Tagliaferri, S.; Caglieri, et al., A. (Acta Biomedica Atenei Parmensis, 2009)
Polybrominated diphenyl ethers (PBDEs) are an important class of flame retardants, widely used in a variety of consumer products. In the past several years, PBDEs have become widespread environmental pollutants, and have been detected in water, soil, air, animals and human tissues. Exposure occurs in particular through the diet and the indoor environment. Infants and toddlers have the highest body burden, due to exposure via maternal milk and through house dust. Tetra-, penta- and hexa-BDEs are the congeners most commonly found in humans. Recent concerns on possible adverse health effects of PBDEs are focusing on their potential endocrine disrupting effects and on developmental neurotoxicity.